Implicit and explicit compromises in long-term partner choice - Williams, Melinda; Sulikowski, Danielle (Personality and individual differences, 2020)
AbstractIndividuals select mates adaptively, adjusting their ideal partner preferences in accordance with their own mate value, and prevailing environmental conditions. They may then select a mate that falls short of these preferences if they are unable to locate or attract someone who meets their ideals. In the current study we investigated the extent to which men and women of varying mate value compromise their mate choice decisions implicitly (by lowering their preferred ideals) or explicitly (by choosing a partner who falls short of their declared). Participants reported on their ideal trait preferences, the traits of an actual long-term partner, and their own mate value. We observed that both men and women engaged in substantial implicit compromise, with lower stated ideal preferences across all potential partner traits, as participant self-perceived mate value decreased. Explicit compromises were comparatively rare and unrelated to an individual's own mate value. We conclude that implicit compromise from both men and women plays a far greater role than does explicit compromise in either sex in driving assortative mating.